A New Hybrid Whale Optimization Algorithm for Green Vehicle Routing Problem. Issue 1 (1st January 2021) - Dewi, Shanty Kusuma; Utama, Dana Marsetiya
Abstract : In recent years, issues on global warming and climate change have received public attention. One of the causes of this problem is carbon emissions in the transportation sector. Therefore, a proper route can reduce this problem. This article aims to develop the Hybrid Whale Optimization Algorithm (HWOA) to minimize the distribution cost of the Green Vehicle Routing Problem (GVRP). The proposed algorithm is based on the Whale Optimization Algorithm (WOA) algorithm combined with the Tabu search algorithm and local search procedures. In the proposed HWOA algorithm, 10% of the whale search agents were adjusted according to the Tabu Search heuristic procedure. A local search was applied to improve the algorithm's quality. Furthermore, a numerical experiment is carried out to test the proposed algorithm. The experiments are conducted to determine the effect of parameters and various speeds on total distribution cost and computation time. Moreover, The proposed algorithm is also compared to some previous algorithms. The findings showed that HWOA is more competitive in minimizing the total distribution cost of GVRP as compared to other algorithms.